A synthesis of 15 years of instream woody habitat management: Progress towards benchmarks and assessing fish responses. (20th July 2022) - Hale, Robin; Kitchingman, Adrian; Sharley, Joanne; Reich, Paul; Tonkin, Zeb
Abstract: There is increasing focus globally on restoration actions to mitigate the effects of humans on freshwater ecosystems. Given the substantial investments in these actions, there is a need to determine if they meet their intended ecological outcomes. Setting benchmarks and rigorous monitoring of responses to actions are essential but are often not undertaken. Addition of instream woody habitat (IWH) is one of the most common stream rehabilitation techniques globally, particularly with the aim of enhancing fish populations. We present a synthesis of IWH interventions undertaken over a 15‐year period across the state of Victoria, in south‐eastern Australia. We collated data from 275 rivers on past IWH densities and, using benchmarks that had been set in earlier work, we examined how much current IWH levels deviated from this benchmark (Aim 1), as a way of assessing where IWH is degraded relative to estimated natural levels, and quantified progress towards achieving IWH benchmarks (Aim 2). We then used data from 25 intervention projects to assess fish responses to IWH additions using a meta‐analysis (Aim 3), including exploring the role of several predictors (time since intervention, baseline habitat density) on the magnitude of these responses. Many rivers had lower IWH densities than their benchmarks. The density of IWH had increased by less than 20% in many waterways where IWH had been added. However, at some locations, IWH additions had led to density increases of more than 40%. Fish responses to IWH additions were mixed overall but we found evidence that positive effects are more likely at locations older than 8 years post‐intervention, and those in areas with higher IWH density prior to additions. Our study highlighted: (1) deriving benchmarks can help set clear management targets, and facilitate meaningful evaluation of progress; and (2) fish responses to IWH additions may take several years (at least) to occur, and response trajectories can be non‐linear, including the potential for short‐term negative outcomes. Therefore, a long‐term commitment to monitoring and evaluation is needed. Consideration of these points will help river managers decide where to focus their efforts to maximise ecological responses to IWH additions and other restoration actions more broadly.